UNIVERSITY STUDENTS RESPONSES’ TOWARDS THE USE OF PHET-BASED VIRTUAL LABORATORY ON THE BASIC OF SCIENCE CONCEPTS COURSE - Natsir, Siti Zahra Mulianti; Sahabuddin, Erma Suryani; Syamsuddin, Afdhal Fatawuri (Universitas Pakuan, 2025)
The rapid development of educational technology has brought significant changes to science learning, primarily by integrating virtual laboratories. These tools provide interactive and student-centered experiences that are more accessible than conventional labs. This study explores the importance of PhET-based virtual labs in enhancing students' understanding of energy and work concepts in a Basic Science Concepts course, emphasizing their relevance in modern, inquiry-based science education. This research analyzes university students’ perceptions of the usability and quality of PhET simulations used in the course. Using a quantitative survey method, data were collected from 161 randomly selected university students through a Likert-scale questionnaire. The results show an overall satisfaction rate of 71.68%, indicating a positive response categorized as